Sensitivity analysis of xylose production process using aspen plus - N H, Ibrahim; W H, W Ibrahim; Mimi Sakinah, A. M.; N., Harun; M R, Othman (IOP Publishing, 2020)
Abstract. Xylose production has become one of the most studied process over the year due to the significant application as a raw material for the production of a variety of specialty chemicals, mainly xylitol. The most promising raw material is lignocellulosic biomass because of its widely available and cheap. There are several type of pretreatment process has been studied to depolymerized the lignocellulosic compounds into fermentable sugars. Among all, dilute acid hydrolysis is the most promising process to produce high xylose. However, disadvantage of this pretreatment process is production of byproduct that can slowdown the fermentation step. Understanding the effect of pretreatment processing parameters on lignocellulosic depolymerization could possibly result in minimization of degradation compounds. Therefore, the aim of this work is to carry out the sensitivity analysis of the acid hydrolysis process used for the production of fermentable sugars with the aid of Aspen Plus by considering the concentration of xylose, glucose, furfural and acetic acid obtained at the outlet of reactor as the output variable. Sensitivity analysis were apply at temperature (160 °C, 170 °C and 180 °C) and residence time (0-160 min). The results indicate that the developed process model is possible to improve lignocellulosic conversion efficiency while minimizing degradation product generation with the highest xylose produce is 18.26 g/L at 180 °C during 20 min reaction time.